PERTUNJUKAN TEATER “LETTING GO” TERINSPIRASI DARI KASUS KRISIS IDENTITAS PADA SEORANG AKTOR (EKSPLORASI MAKE-UP SEBAGAI PERUBAHAN IDENTITAS ) - Vita Oktaviana; Maria Ludvina Koli (Jurnal Ilmu Budaya, 2024)
The work of an actor is not an easy thing to do because it requires various processes that are not simple to be able to play a character. Although. every actor has their own way to prepare the character that is about to play, they must be able to take the right approach both physically and psychologically to learn and get into a character. However, after the performace some actors have often experienced difficulties letting go of the character that has been played. This study aimed to shed light on a phenomenon that often occurs to actors and also to created a theater performance to represent identity crisis that happened in the actors field. The method used in this study is the qualitative method by using descriptive analysis, which aims to interpret the problem under this study understandably. This study revealed that it is true there is an identity crisis issue happening in actors field, which at the end was also gave a rise to a theatrical performance entitled “Letting Go”. That tells a story about the other side of a middle-aged woman’s life named Kana who is also an actor in her young. The performance that shows how that middle-aged woman struggle to balance the live between her actor’s lives (in her glorious era) and her actual lives. This art explores the use of make-up as a different approach from other arts. Keywords : identity crisis; actors; make-up